(untitled) (Bioagro, 2024)
The fruits of the genus Passiflora are mainly found in the Americas, and are characterized by an important bioactive content. Therefore, this study aimed to study the changes in the level of total polyphenols, carotenoids, and antioxidant activity in fruits of Passiflora tripartita (var. Mollisima) known as "pur-pur", in four localities of northeastern Peru (Amazonas department). For this purpose, fruits were collected at three stages of maturity (according to fruit color), and the soluble solids content, titratable acidity, antioxidant activity (by DPPH assay), total polyphenols (PFT, by Folin-Ciocalteu assay) and total carotenoids (CCT) of the pulp (pure) and peel of the fruit were evaluated. Our study determined that total polyphenol content decreases during maturity (peel showed higher PFT than pulp). Carotenoid content and antioxidant activity reached 30.4 and 89.96%, 29.74 μg/g, and 88.06% in pulp and peel, respectively. In addition, it was possible to determine that the maturity stage influences the antioxidant activity (P≤0.05), which, in turn, is linearly correlated with the carotenoid content.